Factors Contributing the Transformation in Animal Husbandry in India: With Special Reference to Mysuru District in Karnataka - Madhukumari G.M.; J.L. Banashankari, (ಅಕ್ಷರಸೂರ್ಯ (AKSHARASURYA), 2025)
India, the world’s largest milk producer and second-largest producer of fruits and vegetables, has been progressively strengthening its agricultural and animal husbandry sectors to meet both domestic and global demands. The animal husbandry sector has undergone a notable transformation in recent decades, driven by increased production of milk, eggs, and meat, adoption of modern technologies, and supportive government initiatives. Modernizing the sector is crucial to overcoming challenges such as low productivity, poor animal health, and limited market access, which have traditionally constrained rural livelihoods. This study focuses on examining the status and trends in animal husbandry in India and analyzing the key factors contributing to its transformation. Primary data were collected from 60 livestock farmers in Mysore district through structured questionnaires and interviews.
Keywords: Animal Husbandry; Transformation; Rural Livelihood